2020
DOI: 10.3390/ph13090223
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Contribution of P-Glycoprotein in the Protective Effect of Paeonol against Methotrexate-Induced Testicular Injury in Rats

Abstract: Paeonol, a phenolic ingredient in the genus Paeonia, possesses antioxidant and anti-inflammatory effects. Methotrexate (MTX) is a commonly used chemotherapeutic agent; however, its germ cell damage is a critical problem. P-glycoprotein (P-gp), an efflux transporter, is a member of the blood–testis barrier. The present study evaluated the protective effect of paeonol on MTX-induced testicular injury in rats with the exploration of its mechanism and the possible contribution of P-gp in such protection. Testicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…Caspase 3, is a crucial enzyme in programmed cell death pathway is implicated in germ cell apoptosis with MTX administration [27]. In current work, MTX-induced caspase-3 expression in testis, which agrees with [21] who reported that MTX-induced elevation in caspase 3 immunostaining. Induction of oxidative stress and in ammation are two supposed mechanisms induce apoptosis of testicular cells [28].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Caspase 3, is a crucial enzyme in programmed cell death pathway is implicated in germ cell apoptosis with MTX administration [27]. In current work, MTX-induced caspase-3 expression in testis, which agrees with [21] who reported that MTX-induced elevation in caspase 3 immunostaining. Induction of oxidative stress and in ammation are two supposed mechanisms induce apoptosis of testicular cells [28].…”
Section: Discussionsupporting
confidence: 90%
“…In current study, after administration of MTX, cellular TNF-α activity signi cantly increased. Many studies illustrate that, TNF-α has a role in the pathogenesis of MTX-induced testicular injury [21].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the MEPGL may either enhance the production of GSH and/or may decrease the oxidative stress resulting in a reduction in GSH levels. The protection of GSH is by scavenging the free radicals, acting as a cofactor for antioxidant enzymes, and accelerating the xenobiotic detoxification [ 42 ]. GPx reacts with various lipid hydroperoxides that are generated during lipid peroxidation and it enhances the reduction of hydrogen peroxide in the presence of GSH to water.…”
Section: Discussionmentioning
confidence: 99%
“…Few in vitro studies have shown that paeonol might modulate the expression of efflux transporters that accept MTX as a substrate, such as BCRP and P-gp (Zhang et al, 2015). One recent in vivo study reported that paeonol could affect testicular expression levels of P-gp (Morsy et al, 2020a). Paeonol seems to act as an "adaptogen."…”
Section: Introductionmentioning
confidence: 99%